2007
DOI: 10.1016/j.freeradbiomed.2006.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants in cystic fibrosis☆Conclusions from the CF Antioxidant Workshop, Bethesda, Maryland, November 11-12, 2003

Abstract: Although great strides are being made in the care of individuals with cystic fibrosis (CF), this condition remains the most common fatal hereditary disease in North America. Numerous links exist between progression of CF lung disease and oxidative stress. The defect in CF is the loss of function of the transmembrane conductance regulator (CFTR) protein; recent evidence that CFTR expression and function are modulated by oxidative stress suggests that the loss may result in a poor adaptive response to oxidants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 179 publications
(195 reference statements)
2
61
0
Order By: Relevance
“…Determination of serum Zn is by far the most accessible way but the results are influenced by many factors such as inflammation, nutrition and age. Despite these limitations many supplementation studies use serum Zn values to ascertain intake and later on look at clinical effects indirectly or partially related to the Zn status [20] . In our observation the median serum Zn value of the low-Zn supplemented cohort was 63.5 (13.0) g/dl before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of serum Zn is by far the most accessible way but the results are influenced by many factors such as inflammation, nutrition and age. Despite these limitations many supplementation studies use serum Zn values to ascertain intake and later on look at clinical effects indirectly or partially related to the Zn status [20] . In our observation the median serum Zn value of the low-Zn supplemented cohort was 63.5 (13.0) g/dl before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being major sources of intracellular oxidants, pulmonary cells are exposed to ϳ8000 L of oxygen-rich air daily as well as toxic particles [4]. Recent studies indicate that diesel exhaust exacerbates influenza virus infections in respiratory epithelial cells [5].…”
mentioning
confidence: 99%
“…These protective effects of selenium seem to be primarily associated with its presence in the GSH-Px and thioredoxin reductase, which are known to protect DNA and other cellular components from oxidative damage (Cantin et al 2007). Generally, seleno-enzymes are known to play an important role in the control of cell division, oxygen metabolism, detoxification process, additionally, in vitro studies have shown that selenium compounds are able to inhibit oxidative stress (Schweizer et al 2004).…”
Section: Resultsmentioning
confidence: 99%